2015
DOI: 10.1590/1807-3107bor-2015.vol29.0132
|View full text |Cite
|
Sign up to set email alerts
|

Validation of micro-computed tomography for occlusal caries detection: an in vitro study

Abstract: Conventional methods of caries detection, including the gold standard of histological examination, have certain disadvantages that must be addressed prior to validating any other diagnostic technique-current or new. Here we evaluated the validity of micro-computed tomography (micro-CT) as an alternative gold-standard technique for caries detection. Sixty teeth with suspected occlusal caries were chosen from a pool of teeth extracted for orthodontic, periodontal, or surgical reasons. Identical reference points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 24 publications
(46 reference statements)
4
33
0
Order By: Relevance
“…This was also the case for conceptual papers and other reviews (not primary studies). Neuhaus et al [2011] 0.73 (0.21, 1.25) Jallad et al [2015] 0.88 (0.80, 0.96) Ekstrand et al [2011] 0.96 (0.83, 1.09) Diniz et al [2011] 0.89 (0.86, 0.92) Souza et al [2013] 0.92 (0.72, 1.12) Gomez et al [2013] 0.85 (0.56, 1.14) Cotta et al [2015] Ekstrand et al [2011] 0.91 (0.78, 1.04) Castilho et al [2016] 0.60 (0.24, 0.96) Ozkan et al [2015] 0.76 (0.38, 1.14) Ko et al [2015] 0.96 (0.94, 0.96) Ekstrand et al [2007] 0. 85 (0.65 Forest plots for meta-analysis and heterogeneity analysis of intra-and inter-examiner reproducibility when ICDAS was used for assessing caries lesion severity.…”
Section: Systematic Review: the Accuracy Of The Icdas In Detectingmentioning
confidence: 99%
“…This was also the case for conceptual papers and other reviews (not primary studies). Neuhaus et al [2011] 0.73 (0.21, 1.25) Jallad et al [2015] 0.88 (0.80, 0.96) Ekstrand et al [2011] 0.96 (0.83, 1.09) Diniz et al [2011] 0.89 (0.86, 0.92) Souza et al [2013] 0.92 (0.72, 1.12) Gomez et al [2013] 0.85 (0.56, 1.14) Cotta et al [2015] Ekstrand et al [2011] 0.91 (0.78, 1.04) Castilho et al [2016] 0.60 (0.24, 0.96) Ozkan et al [2015] 0.76 (0.38, 1.14) Ko et al [2015] 0.96 (0.94, 0.96) Ekstrand et al [2007] 0. 85 (0.65 Forest plots for meta-analysis and heterogeneity analysis of intra-and inter-examiner reproducibility when ICDAS was used for assessing caries lesion severity.…”
Section: Systematic Review: the Accuracy Of The Icdas In Detectingmentioning
confidence: 99%
“…In fact, a recent study has shown that this method correlates well with a histological gold standard (0.917 for accuracy and 0.949 for AUC) when visual scores for the presence of caries are compared. 9 Some advantages of the micro-CT method is that it is non-destructive and provides mineral density values as outcomes of caries presence instead of possibly relying on dentin reactions to caries rather than on the effect of tissue demineralization. 10 Moreover, micro-CT allows threedimensional visualization and quantification of sound and diseased tissues.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although most studies on sensitivity, specificity, reproducibility, and accuracy of dental caries diagnostic tools are performed against a histological gold standard (stereomicroscopy), 8 more recently, laboratory non-destructive methods have been proposed as possible surrogate gold standards for detection of carious lesions. 9 Histological detection of caries has some limitations, including the destructive and two-dimensional approach, difficulties in discriminating between histological dentin reactions and true demineralization, 10 and the applied qualitative-based scoring system, which may vary among studies. 11,12 Micro-CT is a laboratory non-destructive technique which allows reconstruction of linear attenuation coefficients measured from a series of X-ray projections into a pattern of gray scale values throughout the object's volume.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, µCT provides nonoverlapping 3D imaging of the dental structure where mineral density can be estimated in large volume areas. Prior studies have validated µCT for the detection of occlusal and proximal caries [Mitropoulos et al, 2010;Taylor et al, 2010;Soviero et al, 2012;Ozkan et al, 2015], and more recently it has been reported to be an alternative to histological sectioning of carious tissue [Boca et al, 2017]. Despite the differences between methods, there were outcome similarities for the high remineralization (A, B, and C mints and GT) and low remineralization (xylitol) groups.…”
Section: Discussionmentioning
confidence: 99%